The Influence of Eracs and Non Eracs Sectio-Caesarea Delivery Methods on Early Mobilization Time of Post Partum Mothers - Elsa Nuristiawati Adha; Nur Anita (Global Health Science Group, 2023)
In order to reduce the number of complications and morbidity, several developed and developing countries such as Indonesia began to apply methods that can reduce the risk of complications so that the length of hospitalization and the healing and mobilization process become faster known as the Enhanced Recovery After Cesarean Section (ERACS) method. The purpose of this study was to analyze the effect of the secio operation method on the time of early mobilization start. This research design was of observational resrospective monitoring for 3 years. The location used for this research is in BPM Hj. Nurjanah ST and BPM Nurkholilah STr.Keb Pematang Village, Pematang District, Serang Regency. This research was conducted in May 2023. The samples used in this study used a total sampling of 43 samples. The analysis used is by linear regression test. The conventional secio group (Non ERACS) the average time needed for mobilization was 6.5 hours while in the ERACS secio group the average mobilization time was 2 hours faster which was 4 hours. The results of linear regression analysis obtained p values of 0.003 < 0.05 which means that the ERACS cesarean cesarean method can accelerate mobilization time in patients and is statistically significant.